Comparison of Cell Viability and Chemical Composition of Six Latest Generation Orthodontic Wires - Lina M. Escobar; Jaime Rodrigo Rivera; Eliana Arbelaez; Luisa F. Torres; Andrea Villafañe; David Díaz-Báez; Ingrid Mora; Gloria I. Lafaurie; Midori Tanaka (International Journal of Biomaterials)
Orthodontic wires are made of alloys containing different metals, including nickel. It is important to evaluate their biocompatibility prior to use, owing to their long-term use in patients. This in vitro study compared the cytotoxicity and chemical composition of six latest orthodontic wires: Fantasia®, Tanzo®, FLI®, NT3®, DuoForce®, and Gummetal®. The before-use group consisted of wires that were not used in the mouth, and the after-use group consisted of wires that were used in the mouth for two months. The wires were placed in contact with human gingival fibroblasts (HGF) for 72 h, and cytotoxicity was determined using the resazurin test. The chemical composition and surface characterisation were evaluated by spectrometry and scanning electron microscopy. The groups were compared using ANOVA and Kruskal–Wallis test. Only the FLI® wires produced a 36% reduction in HGF viability (p<0.05) and presented greater irregularities and loss of polymer structure. After-use wires showed a significant reduction in the percentage of nickel and the appearance of new elements (oxygen and carbon). Therefore, it can be concluded that no toxic ion release was noticed in this study. Rhodium-coated wires were more stable than PTFE-coated wires, and only the FLI® wires showed a slight cytotoxic effect.